Extended psychological help in the Icelandic upper secondary school system? : adolescent students need for psychological help and their attitude towards psychological help - Þorkell Magnússon 1990- (2017)
Increasing rates of depression and anxiety disorder are of growing concern in the health care community. The burden of mental health problems can have immense consequences and can be seriously disabling for those dealing with them. There is a lack of research into adolescents’ attitudes towards psychological services in Iceland. Attitudes towards such services seem to have a big effect towards seeking help and offering help to those that are in need. The present study examined Icelandic upper secondary students attitudes towards psychological services. This research looked at differences between different aspects of the adolescents lives, particularly their mental health, and studied if such difference had any impact on the students attitudes towards psychological services. The participants were 565 students from eight upper secondary schools in Iceland. The age range was from 18 years old to 25 years old or older, mean age was 19,34 years. Males were 197 and females 368. Results show that there are very little differences between the views of different groups of adolescent students if any difference exists. Results also show that Icelandic adolescents believes about psychological services are generally very positive. Keywords: adolescents, upper secondary schools, depression, anxiety, believes about psychological services. Aukin tíðni þunglyndistilfella og kvíðaröskunar vekja athygli í heilbrigðisgeiranum. Geðræn vandamál og geðsjúkdómar geta haft lamandi áhrif á líf þeirra sem við þau glíma. Það skortir verulega á rannsóknir á viðhorfum ungs fólks til sálfræðiþjónustu á Íslandi. Viðhorf til slíkrar þjónustu virðist hafa mikil áhrif á það hvort fólk leitar sér aðstoðar og hvernig hægt er að bjóða aðstoð til þeirra sem það þurfa. Þessi ritgerð fjallar um rannsókn sem gerð var meðal íslenskra framhaldsskólanemenda þar sem könnuð voru viðhorf þeirra til þjónustu sálfræðinga. Í rannsókninni var kannað hvort munur væri á viðhorfum út frá ýmsum þáttum í lífi ungmenna. Þá var geðheilsa þeirra sérstakt ...